2022
DOI: 10.1111/mmi.15002
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin: A universal host cytoskeletal target of Gram‐negative and Gram‐positive bacterial pathogens

Abstract: Upon infection, many microbial pathogens exploit the host's actin cytoskeleton (Dowd et al., 2021;Pollard & Cooper, 2009;Stradal & Costa, 2017). One of the favorite targets of pathogens to take control over the host cytoskeleton is the prominent actin-binding protein cortactin. Cortactin plays a major role in cytoskeletal dynamics and secretion of extracellular matrix proteins in healthy cells, but also in disease development including cancers, cardiovascular diseases, blood-brain barrier malfunctions, and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 123 publications
1
8
0
Order By: Relevance
“… 42 It has also been reported that WASP, the Dictyostelium N-WASP homolog, is able to restrict Rac1 activity, 43 and it is well established that Rac1 is a key driver of S. Tm uptake. 44 Many other invasive bacteria and viruses activate N-WASP during the course of their own infection of host cells 45 and it will be intriguing to explore the role of N-WASP in these systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 42 It has also been reported that WASP, the Dictyostelium N-WASP homolog, is able to restrict Rac1 activity, 43 and it is well established that Rac1 is a key driver of S. Tm uptake. 44 Many other invasive bacteria and viruses activate N-WASP during the course of their own infection of host cells 45 and it will be intriguing to explore the role of N-WASP in these systems.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we show that rather than driving the entry of Salmonella into non-phagocytic cells, the Cdc42-N-WASP pathway, activated by the delivered effector SopE2, is instead inhibitory to pathogen uptake. N-WASP activation has been implicated in the invasion of host cells by many intracellular bacterial pathogens, 45 though as is the case for S. Tm, the direct evidence for this is often lacking. In fact, in at least one of these cases, namely Shigella flexneri , it has also been reported that exogenous expression of N-WASP is inhibitory to pathogen entry, 26 as we describe here for Salmonella .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although cortactin alone can weakly activate the Arp2/3 complex, it synergizes with class 1 NPFs to further stimulate efficient Arp2/3-mediated formation of actin branches 21 , 22 , 34 . Given its central role in stabilizing branched actin networks, cortactin is important in many cellular processes such as epithelial integrity and intracellular trafficking, as well as a range of pathologies, including bacterial infection and cancer metastasis 29 , 35 37 . However, despite its functional importance, the precise mode of action of cortactin and its mechanism of synergy with class 1 NPFs remain unknown.…”
Section: Mainmentioning
confidence: 99%
“…neuronal WASP (N-WASP) ( Fregoso et al., 2023 ; Martinez-Quiles et al., 2004 ). Various functions of cortactin are regulated by post-translational modification events e.g., phosphorylation or acetylation ( Schnoor et al., 2018 ; Sharafutdinov et al., 2022c ). Serine phosphorylation of cortactin at S113, S405 and S418 by p21-associated kinase (PAK) and extracellular regulated 1–2 (Erk1/2) kinases, and tyrosine phosphorylation at Y421, Y470 and Y486 by Src, Syk, Fer and Abl kinases control cortactin's interaction partners and downstream signaling.…”
Section: Introductionmentioning
confidence: 99%